A complex microcephaly syndrome in a Pakistani family associated with a novel missense mutation in RBBP8 and a heterozygous deletion in NRXN1 - Agha, Zehra; Iqbal, Zafar; Azam, Maleeha; Siddique, Maimoona; Willemsen, Marjolein H.; Kleefstra, Tjitske; Zweier, Christiane; De Leeuw, Nicole; Qamar, Raheel; Van Bokhoven, Hans (Gene, 2014)
We report on a consanguineous Pakistani family with a severe congenital microcephaly syndrome resembling the Seckel syndrome and Jawad syndrome. The affected individuals in this family were born to consanguineous parents of whom the mother presented with mild intellectual disability (ID), epilepsy and diabetes mellitus. The two living affected brothers presented with microcephaly, white matter disease of the brain, hyponychia, dysmorphic facial features with synophrys, epilepsy, diabetes mellitus and ID. Genotyping with a 250K SNP array in both affected brothers revealed an 18 MB homozygous region on chromosome 18 p11.21-q12.1 encompassing the SCKL2 locus of the Seckel and Jawad syndromes. Sequencing of the RBBP8 gene, underlying the Seckel and Jawad syndromes, identified the novel mutation c.919A>G, p.Arg307Gly, segregating in a recessive manner in the family. In addition, in the two affected brothers and their mother we have also found a heterozygous 607kb deletion, encompassing exons 13-19 of NRXN1. Bidirectional sequencing of the coding exons of NRXN1 did not reveal any other mutation on the other allele. It thus appears that the phenotype of the mildly affected mother can be explained by the NRXN1 deletion, whereas the more severe and complex microcephalic phenotype of the two affected brothers is due to the simultaneous deletion in NRXN1 and the homozygous missense mutation affecting RBBP8.
EVALuna2:9226